The Effects of Budget Deficit on Economic Growth and Development: The Experience of Ghana (1994 – 2014) - Napoleon Kurantin (European Scientific Journal, ESJ, 2017)
This paper surveyed and access the empirical literature on the sources of budget deficit and their policy implications on the processes of sustainable economic growth and development. The Ghanaian experience and evidence shows that the budget is not projected to be on a sustainable growth path under current socio-economic and political (governance) policies; the budget is projected to increase more quickly than the country’s Gross Domestic Product (GDP). The modeling of underlying variables (Inflation, Gross Domestic Product, Real Interest Rate, Gross Investment, Real Exchange Rate) to estimate the quantitative effect of continued budget deficit on the rate of economic growth, governance and development. The sample used for this study is based on panel data-sets between 1994 and 2014. Results obtained from the analysis pointed to an adverse impact of continued budget deficit on the processes of economic growth and development. The paper recommends the adoption and implementation of policies that could reverse the un-sustained budget deficit leading to crowding out of the private investment but rather, put the economic on a sustained path of growth and, development in the medium to long term.